2019
DOI: 10.1002/pds.4849
|View full text |Cite
|
Sign up to set email alerts
|

Do the 2015 Beers Criteria predict medication‐related harm in older adults? Analysis from a multicentre prospective study in the United Kingdom

Abstract: Purpose To investigate whether inappropriate prescribing, defined by the Beers Criteria, is associated with medication‐related harm (MRH), hospital admission, and mortality in older adults in England. Methods A multicentre, prospective cohort study recruited 1280 patients (median age 82 years) at hospital discharge. Patients were followed‐up in the community by pharmacists for 8 weeks to identify MRH (harm from adverse drug reactions, non‐adherence, and medication errors) and hospital admissions. One‐year mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
1
24
2
Order By: Relevance
“…Of these, 103 articles were excluded, mainly because studies reported a different outcome of interest ( n = 58). The final screening identified 63 studies 33–95 suitable for inclusion in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 103 articles were excluded, mainly because studies reported a different outcome of interest ( n = 58). The final screening identified 63 studies 33–95 suitable for inclusion in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies measured the association between PIP and mortality 36,37,41,43,48,56,57,60,69,72,77–79,81,82,84–85,93 . Four studies reported in‐hospital mortality, 48,77–79 the remainder assessed mortality outcome after hospital discharge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…inappropriate medicine and the Beers Criteria have limited value to predict adverse clinical outcomes in the United Kingdom settings. 1 In 2018, we conducted a retrospective, cross-sectional study of prescriptions of 477 patients aged 65 years and above who were taking at least five or more medications. Out of this cohort, a total of 65 (13.6%) patients were prescribed one or more PIMs based on the American Geriatrics Society 2015 Beers Criteria (Table 1).…”
mentioning
confidence: 99%